Risk Communication - Shaw, Rajib; Takeuchi, Yukiko; Matsuura, Shohei; Saito, Keiko (World Bank, Washington, DC, 2013)
Risk communication is an important component of disaster risk management (DRM) because it shapes people's perceptions of risk and influences their actions with respect to disaster preparedness and disaster response. It also influences the intervention decisions that are made throughout the disaster management cycle. The credibility of the information source takes a long time to build and needs to be well established before a disaster strikes. In Japan, the level of trust in government and other official communications was sorely tested following the nuclear accident at the Fukushima Daiichi nuclear power station. Successful risk communication occurs when there is holistic learning, facilitation, and trust. In holistic learning, the gap in knowledge between the information sender and receiver is minimal. Hazard maps, booklets, and videos can all help narrow that gap when it comes to disaster education and risk communication. This report gives findings; lessons; and recommendations for developing countries.